Estudo da anomalia de Pelger-Huët em núcleo familiar - Calderan, Patrícia H. O.; Campiolo, Dimas J.; Saavedra, Omar S. G.; Bonini-Domingos, Claudia Regina [UNESP] (My University, 2008)
The Pelger-Huët anomaly is a dominant autosomal disease, characterized by the incomplete segmentation of the granulocytes nucleus without lost of the cellular function. The heterozygotes form of this anomaly is assintomatic and it did not possess physic meant, while the homozygote form is rare and can be lethal, being therefore, important differentiates of other infectious alterations. The pseudoanomaly can occasionally be observed in cases of granulocitic leukemia, mieloproliferatives Diseases, some infections and after exposition the determined drugs. We evaluate eleven members of a familiar nucleus and, after the blood cells analysis, six of then had presented neutrophils and eosinophils with nuclei characteristic of the heterozygotes form of the Pelger-Huët anomaly. The recognition of this leukocyte anomaly, mainly in patients without infection and presenting great number of not segmented neutrophils, can prevent wrong interpretations of the blood cells count and unnecessary clinical and therapeutically behaviors.
Pelger-Huët anomaly study in a family
Keywords: Leukocite abnormalities; Pelger-Huët